Lower corticospinal excitability and greater fatigue among people with multiple sclerosis experiencing pain. Issue 1 (January 2023) - Murphy, Hannah M.; Fetter, Christopher M.; Snow, Nicholas J.; Chaves, Arthur R.; Downer, Matthew B.; Ploughman, Michelle
Introduction: Persons with multiple sclerosis (MS) frequently report pain that negatively affects their quality of life. Evidence linking pain and corticospinal excitability in MS is sparse. We aimed to (1) examine differences in corticospinal excitability in MS participants with and without pain and (2) explore predictors of pain. Methods: Sixty-four participants rated their pain severity on a visual analog scale (VAS). Transcranial magnetic stimulation (TMS) and validated clinical instruments characterized corticospinal excitability and subjective disease features like mood and fatigue. We retrieved information on participants' prescriptions and disability status from their clinical records. Results: Fifty-five percent of participants reported pain that affected their daily functioning. Persons with pain had significantly greater fatigue and lower area under the excitatory motor evoked potential (MEP) recruitment curve (eREC AUC), a measure of total corticospinal excitability. After controlling for age, disability status, and pain medications, increased fatigue and decreased eREC AUC together explained 40% of the variance in pain. Discussion: Pain in MS is multifactorial and relates to both greater fatigue and lesser corticospinal excitability. Future work should better characterize relationships between these outcomes to develop targeted pain interventions such as neuromodulation. Summary: We examined pain in MS. Individuals with pain had higher fatigue and lower corticospinal excitability than those without pain. These outcomes significantly predicted self-reported pain.